2018
DOI: 10.1021/acsbiomaterials.7b00714
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Disulfide Nanoparticles Resist Oxidative Stress-Mediated Impairment of Autophagic Flux and Mitigate Endothelial Cell Senescence and Angiogenic Dysfunctions

Abstract: The impairment of autophagy involves oxidative stress-induced cellular senescence, leading to endothelial dysfunctions and the onset of cardiovascular diseases. As molybdenum disulfide nanoparticles (MoS 2 NPs), representative transition metal dichacogenide materials, have great potential as a multifunctional therapeutic agent against various disorders, the present study aimed to investigate whether MoS 2 NPs prevents hydrogen peroxide (H 2 O 2 )induced endothelial senescence by modulating autophagic process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 50 publications
3
42
0
Order By: Relevance
“…Obviously, the nucleation of PLLA crystallites during the solvent evaporation was a prime factor in enhancing the mechanical properties of the polymer matrix. This study, together with the fact that these nanotubes are found to exhibit minor toxicity [34][35][36][37][38], opens up several opportunities to further explore these nanocomposites for different applications.…”
Section: Raman Spectroscopymentioning
confidence: 88%
See 1 more Smart Citation
“…Obviously, the nucleation of PLLA crystallites during the solvent evaporation was a prime factor in enhancing the mechanical properties of the polymer matrix. This study, together with the fact that these nanotubes are found to exhibit minor toxicity [34][35][36][37][38], opens up several opportunities to further explore these nanocomposites for different applications.…”
Section: Raman Spectroscopymentioning
confidence: 88%
“…Furthermore, the addition of the nanotubes to different gels [32,33] and polymer matrices [34] in small amounts leads to a precipitous reduction in the friction forces, which may have important ramifications on numerous medical and other technologies. Equally important is the fact that several studies have indicated that IF/INT of WS 2 (MoS 2 ) are non-toxic and biocompatible [34][35][36][37][38]. One of the challenges in nanocomposites is the compatibility between the polymer matrix and the nanofillers, which entails that the interfacial interaction between the surfaces of the two phases cannot be easily tuned and matched.…”
Section: Introductionmentioning
confidence: 99%
“…Several other strategies have been recently proposed to provide more accurate and targeted senolytic-based interventions. These include nanotechnology-based approaches for detection, site-specific delivery of senolytics and/or senoprobes, and successful elimination of SCs [ 83 , 107 , 108 , 109 , 110 ]. As cellular senescence may be implicated in the pathogenesis of age-related neurodegenerative diseases such as Alzheimer’s disease and Parkinson’s disease [ 111 , 112 ], the use of nano-senolytics in the central nervous system (CNS) seems promising.…”
Section: Senolytics and Senotherapymentioning
confidence: 99%
“…Functionalized nanomaterials appear to have a promising potential as nanocarriers and can be used for improving SC clearance. Table 1 provides published examples of in vitro and in vivo senotherapeutic action of nano-based drug delivery systems [ 83 , 107 , 108 , 109 , 110 , 114 , 118 , 119 , 120 , 121 ].…”
Section: Nanomaterials For the Clearance Of Senescent Cellsmentioning
confidence: 99%
See 1 more Smart Citation